New development: Citizen science—discovering (new) solutions to wicked problems. Issue 2 (17th February 2022) - Hodgkinson, Ian R.; Mousavi, Sahar; Hughes, Paul
IMPACT: The general population can play a pivotal role in future research endeavours, from the inception of research projects through to delivering research impact. Citizen science is the active, co-participation of the public in scientific research. Through true collaboration, this article shows how citizen science has the potential to discover new solutions to wicked problems. Climate change, extreme poverty, pandemics, health inequalities, and natural disasters are just a few examples of where citizens may hold the key to driving (partial) solutions for a better world.